LINC-10. SIOP PODC ADAPTED TREATMENT GUIDELINES FOR CRANIOPHARYNGIOMA IN LOW- AND MIDDLE-INCOME SETTINGS. (4th December 2020) - amayiri, Nisreen; Spitaels, Ariane; Zaghloul, Mohamed; Figaji, Anthony; Cavalheiro, Sergio; Muller, Hermann L; Elhassan, Moawia; Parkes, Jeannette; Mushtaq, Naureen; El Beltagy, Mohamed; Yousef, Yacoub; Esiashvili, Natia; et al.
Abstract: Pediatric craniopharyngioma is a rare tumor with excellent survival but significant long-term morbidities due to the loco-regional tumor growth or secondary to its treatment. Visual impairment, panhypopituitarism, hypothalamic damage and behavioral changes are amongst the main challenges. This tumor should be managed under the care of a multidisciplinary team to determine the optimum treatment within the available resources. This is particularly important for low middle-income countries (LMICs) where resources are variable. We provide a risk-stratified management guideline for children diagnosed with craniopharyngioma in a resource limited setting based on the service levels describing the facilities and personnel required for management as previously specified by the Pediatric Oncology in Developing Countries (PODC) committee of The International Society of Pediatric Oncology (SIOP). A multi-disciplinary group of neurosurgeons, radiation and pediatric oncologists, radiologists, pediatric endocrinologists and an ophthalmologist with experience in managing children with craniopharyngioma in LMIC setting was formed and carried online meetings to form a consensus guideline. The clinical characteristics (including the visual and endocrine presentations), suggestive radiological features as well as potential treatment options including surgery, radiotherapy and intra-cystic therapies were discussed in depth and in relation to available resources. In addition, hormonal management, pre- and post-operative PICU care and expected future complications related to craniopharyngioma and to follow up these children were discussed and documented in the guideline. We believe this guideline is a useful reference for health care providers in LMIC.